Towards an ordering of the theories of the “communication sciences” - Castillo Hilario, Mario Buenaventura (2020)
The objective of the research was to identify and order the theories of the "communication sciences". For this, a systematic review of the bibliography was carried out. It is concluded that there are four types of autonomous and independent theories: technical, normative, scientific and philosophical.